"A really strong bond": Coaches in women athletes' experiences of inclusion in parasport - Ferguson, J. J.; Spencer, N. L. I. (International Sport Coaching Journal, 2021)
Women within parasport experience discrimination due to marginalization associated with gender and disability. In this study, the authors gain the insights of women parasport athletes about the affordances and constraints to inclusion with an emphasis on the role of coaches, using an ecological approach. Guided by qualitative description, the authors conducted individual and focus group interviews with ten women experiencing disability to explore their experiences and perspectives of inclusion in parasport. Two primary themes were identified: (a) within parasport and (b) beyond parasport, emphasizing the critical role of relationships with coaches and athletes to experiences of inclusion. The discussion highlights the multilevel influences and specific barriers that challenge inclusion, such as few numbers of women athletes, the need for coach expertise, and co-ed playing environments. In doing so, the authors also offer specific recommendations for coaching in women`s parasport.